Between the Virtual and the Actual: Robert Barker's Panorama of London and the Multiplication of the Real in late eighteenth-century London - Otto, Peter (Romanticism on the Net, 2007)
AbstractThe panorama is usually identified as the culmination, for the late eighteenth- and early nineteenth-century, of Enlightenment attempts to produce a “second-order reality in which to play with or practice upon the first order”. It is therefore aligned with the modern attempt to contain everything within a single view or picture. In contrast, this paper argues that in the late eighteenth- and early nineteenth-century the panorama and the hyper-realistic illusions it conjured, paradoxically relied on and at the same time intensified the late eighteenth-century sense that first and second order realities (the “physical environment in which one is really present” and the environments presented by material or textual media) had diverged to a degree that was unprecedented. This at first somewhat counter-intuitive phenomenon occurs not despite but because of the panorama’s ability to simulate the real. The hyper-realistic virtual realities of the early panorama intensified late eighteenth-century interest in the observation of observation; presented perception as an event that did not require the presence of its apparent object, thus radicalising the achievements of Trompe l’Oeil painting; drew attention to the figural space of representation; and provided new evidence for the constructed and contingent nature of the real. The paper takes as its key foci Caspar David Friedrich’s “The Wanderer above a sea of Mists” (1818), the Leicester Square Panorama (opened 1793), and Barker’s panorama of London (1791 and 1795).